INVESTIGATING THE USE OF TECHNOLOGY INTEGRATION AMONG HOME ECONOMICS STUDENTS IN FOOD AND NUTRITION PROGRAM IN COLLEGES OF EDUCATION IN ANAMBRA STATE - Chukwujekwu, Okadigwe John (Universitas Ngeri Malang, 2025)
In today’s digital era, integrating technology into education has become essential for enhancing learning experiences and outcomes. This study adopted a descriptive survey design to investigate the use of technology integration among Home Economics students in Food and Nutrition programs in Colleges of Education in Anambra State. A sample of 55 students was selected through proportionate stratified random sampling. Data were collected using a validated questionnaire (TIFNEQ), with Cronbach Alpha coefficients of 0.86 (awareness), 0.77 (extent of use), and 0.81 (perceived benefits). The researcher personally administered the instrument, achieving a 100% response rate. Data analysis involved descriptive statistics, ANOVA, Duncan post-hoc test, and Pearson correlation, using SPSS version 25, with significance set at the 0.05 level. The study involved 55 Home Economics students, of which (12.7%) were below 20 years, (36.4%) between 20–25 years, (27.3%) aged 26–30, and (23.6%) above 30. By level of study, (16.4%) were in Year I, (27.3%) in Year II, (38.2%) in Year III, and (18.2%) in Year IV. Females represented a majority (89.1%) compared to males (10.9%). In terms of technology availability, the overall mean scores indicated moderate access to tools (mean = 2.96, SD = 1.19), with Year I students reporting the highest availability (mean = 2.73). A significant difference was found across levels of study in technology availability (F (3,51) = 4.03, p = .012). A strong positive correlation existed between availability and extent of use (r = .860, p < .001). Similarly, extent of technology use differed significantly across levels (F (3,51) = 3.33, p = .027), with Year I students again reporting the highest use (mean = 3.11). Perceived benefits of technology also varied significantly (F (3,51) = 3.94, p = .013). A very strong correlation was found between extent of use and perceived benefits (r = .964, p < .001), confirming a meaningful link between practice and value perception. The study concludes that while some digital tools are in use, technology integration is not uniformly implemented, and its potential is underutilized. The study recommends improved provision and equitable access to digital resources to enhance learning in Home Economics